2004
DOI: 10.1128/jvi.78.21.11816-11822.2004
|View full text |Cite
|
Sign up to set email alerts
|

Influence of gag on Human Immunodeficiency Virus Type 1 Species-Specific Tropism

Abstract: The narrow host range of human immunodeficiency virus type 1 (HIV-1) is due in part to dominant acting restriction factors in humans (Ref1) and monkeys (Lv1). Here we show that gag encodes determinants of species-specific lentiviral infection, related in part to such restriction factors. Interaction between capsid and host cyclophilin A (CypA) protects HIV-1 from restriction in human cells but is essential for maximal restriction in simian cells. We show that sequence variation between HIV-1 isolates leads to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
90
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(98 citation statements)
references
References 47 publications
8
90
0
Order By: Relevance
“…The close relatedness between sheep and goats is consistent with the ability of sheep (VMV) and goat (CAEV) lentiviruses to infect both ruminant species (8,32). The high variability of both PRYSPRY (6, 34; this work) and CA of SRLV (7,26) may account for the evolution of both virus and host, involving TRIM5␣ and CA interactions, as described for primate lentiviruses (11,28,34,38). Natural selection in ovine and caprine sequences was determined by estimating (ratio of the rate of nonsynonymous substitutions, dN, to synonymous substitutions, Additional RNA species (6 from a total of 3 sheep) were identified that had a stop codon at residue 347 compared to the full ovine protein TRIM5␣ (OvT5␣), resulting in a reduced number of exons and elongated noncoding sequences at the 3= end, a structure similar to that of human TRIM5␥ (2) (Fig.…”
supporting
confidence: 48%
See 1 more Smart Citation
“…The close relatedness between sheep and goats is consistent with the ability of sheep (VMV) and goat (CAEV) lentiviruses to infect both ruminant species (8,32). The high variability of both PRYSPRY (6, 34; this work) and CA of SRLV (7,26) may account for the evolution of both virus and host, involving TRIM5␣ and CA interactions, as described for primate lentiviruses (11,28,34,38). Natural selection in ovine and caprine sequences was determined by estimating (ratio of the rate of nonsynonymous substitutions, dN, to synonymous substitutions, Additional RNA species (6 from a total of 3 sheep) were identified that had a stop codon at residue 347 compared to the full ovine protein TRIM5␣ (OvT5␣), resulting in a reduced number of exons and elongated noncoding sequences at the 3= end, a structure similar to that of human TRIM5␥ (2) (Fig.…”
supporting
confidence: 48%
“…The close relatedness between sheep and goats is consistent with the ability of sheep (VMV) and goat (CAEV) lentiviruses to infect both ruminant species (8, 32). The high variability of both PRYSPRY (6, 34; this work) and CA of SRLV (7, 26) may account for the evolution of both virus and host, involving TRIM5␣ and CA interactions, as described for primate lentiviruses (11,28,34,38). Natural selection in ovine and caprine sequences was determined by estimating (ratio of the rate of nonsynonymous substitutions, dN, to synonymous substitutions,…”
mentioning
confidence: 99%
“…In humans, the HIV-1 infectivity is enhanced by the interaction of CypA with the capsid (29,30). On the contrary, in other primates, CypA interferes with the viral infection by enhancing the activity of the restriction factors TRIM5α and TRIM-Cyp (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…17 and involves determinants present in the N-terminal domain of the capsid proteins that constitute the retroviral outer core structure. [18][19][20] After this initial contact, progression of the retroviral life cycle is impeded through several mechanisms. Viral cores seem to undergo accelerated uncoating, as evidenced by the disappearance of capsid in particulate form.…”
Section: Introductionmentioning
confidence: 99%